Land Management: A Global Perspective - Enemark, Stig (Journal on Geoinformatics, Nepal, 2010)
This article provides an overall understanding of the land management paradigm and the importance of land governance in support of the global agenda. Sustainable land administration systems provide clear identification on the people to land relationship. The land management perspective and the operational component of integrated and spatially enabled land administration systems therefore need high-level political support and recognition.